Ultrasonic-Controled Microlens Arrays in Germanium for Optical Tweezers - Quy, Ho Quang; Thinh, Nguyen Van; Lanh, Chu Van (Communications in Physics, 2015)
The microlens arrays created by ultrasonic waves in acousto-optical material Germanium (Ge) is theoretically proposed. The simulated results show the proposed microlens arrays can be used for optical tweezers arrays to trap an assembly micro-beads. Moreover, with the control by changing of the ultrasonic intensity and frequency, the optical tweezers arrays will act as the dynamical one, which can sieve the beads in (X,Y) plane in the embedding fluid.